Prevalent of Staphylococcus aureus from Sachet Waters Sold in Different Areas of Jos Terminus Market, Nigeria (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Staphylococcus aureus is an important human pathogen that causes wide range of infectious diseases both in nosocomial and community settings. The Gram-positive pathogen possess virulence factors that facilitate it to establish infections in the hosts. When a â€œwater for lifeâ€ is contaminated with infectious bacteria such as Staphylococcus aureus then, there may be public health challenge in the area. In this study Samples of Sachet water of different companies ware purchased, marked E, T, C and R and examined for the presence of staphylococcus aureus. Total of 80 sachet waters were examined and a prevalence rate of Staphylococcus aureus 5(25.00%) was recorded. The study revealed that sachet water (E) has the highest prevalence of 15.00%, followed by T (5%) and C (5%) and R had the least prevalence with 0.00%. It was discovered that a Prevalence rate of Abuja market terminus recorded 1(5.00%) while that of Ahmadu Bello way has the highest prevalence of 2(10.00%), Yan Taya market 1(5.00%) and railway 1(5.00%). This shows that S. aureus can be isolated from sachet waters. Though the sachet eaters had NAFDAC numbers, it is advisable to review and quality control such sachet water companies regularly because of Staphylococcus aureus and other public health infectious agants. The populace should equally be careful with the type of waters they drink.
Keywords: Sachet water; Staphylococcus aureus; Public health; Jos Terminus Market; Nigeria